Role of Rubus chingii BBX gene family in anthocyanin accumulation during fruit ripening - Xu, Zhangting; Zhang, Guihua; Chen, Junyu; Ying, Yuxin; Yao, Lingtiao; Li, Xiaoxian; Teixeira da Silva, Jaime A.; Yu, Zhenming (Frontiers in Plant Science, 2024)
The B-box (BBX) family, which is a class of zinc finger transcription factors, exhibits special roles in plant growth and development as well as in plants' ability to cope with various stresses. Even though Rubus chingii is an important traditional medicinally edible plant in east Asia, there are no comprehensive studies of BBX members in R. chingii. In this study, 32 RcBBX members were identified, and these were divided into five groups. A collinearity analysis showed that gene duplication events were common, and when combined with a motif analysis of the RcBBX genes, it was concluded that group V genes might have undergone deletion of gene fragments or mutations. Analysis of cis-acting elements revealed that each RcBBX gene contained hormone-, light-, and stress-related elements. Expression patterns of the 32 RcBBX genes during fruit ripening revealed that highest expression occurred at the small green fruit stage. Of note, the expression of several RcBBX genes increased rapidly as fruit developed. These findings, combined with the expression profiles of anthocyanin biosynthetic genes during fruit ripening, allowed us to identify the nuclear-targeted RcBBX26, which positively promoted anthocyanin production in R. chingii. The collective findings of this study shed light on the function of RcBBX genes in different tissues, developmental stages, and in response to two abiotic stresses.